Induction of De Novo Subcortical Actin Filament Assembly by Treponema denticola Major Outer Sheath Protein - Amin, Mohsen (American Society for Microbiology, 2004)
Treponema denticola and its major outer sheath protein (Msp) induce actin reorganization in fibroblasts. We adapted a barbed-end labeling/imaging assay to monitor Msp-induced subcortical actin filament assembly in neutrophils and fibroblasts. Msp, at an actin-reorganizing concentration, inhibited migration of these dissimilar cell types, whose cytoskeletal functions in locomotion and phagocytosis are crucial for immunity and healing of peripheral infections.